2017
DOI: 10.1167/tvst.6.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in Cone Density Derived from Gaze-Directed Single Images Versus Wide-Field Montage Using Adaptive Optics Flood Illumination Ophthalmoscopy

Abstract: PurposeWe compared cone density measurements derived from the center of gaze-directed single images with reconstructed wide-field montages using the rtx1 adaptive optics (AO) retinal camera.MethodsA total of 29 eyes from 29 healthy subjects were imaged with the rtx1 camera. Of 20 overlapping AO images acquired, 12 (at 3.2°, 5°, and 7°) were used for calculating gaze-directed cone densities. Wide-field AO montages were reconstructed and cone densities were measured at the corresponding 12 loci as determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Additionally, rapid eye movement and wavefront aberrations that have been unaccounted for in the device may also contribute to reductions in image quality, hence presenting significant challenges to the clinical interpretation of AO-FIO images 32 , 33 . For example, Chew et al have reported exclusion of approximately 40% of images due to image quality in their analyzed data set 16 . Debellemaniere et al had to exclude at least one eye from 46.9% of subjects due to poor AO image quality in their study of patients taking hydroxychloroquine without any evidence of maculopathy 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rapid eye movement and wavefront aberrations that have been unaccounted for in the device may also contribute to reductions in image quality, hence presenting significant challenges to the clinical interpretation of AO-FIO images 32 , 33 . For example, Chew et al have reported exclusion of approximately 40% of images due to image quality in their analyzed data set 16 . Debellemaniere et al had to exclude at least one eye from 46.9% of subjects due to poor AO image quality in their study of patients taking hydroxychloroquine without any evidence of maculopathy 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The images were corrected for magnification error related to axial length (AL) using the modified Littmann’s method described by Bennett et al 15 , where q represents the magnification factor. For more details, refer to Chew et al 16 Regions of interest (ROI) were chosen from retinal loci along the vertical and horizontal meridians. These ROIs were spaced 1° apart between 1° and 10° from the foveal center along each meridian (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To convert metric units to angular units and align the AO montage with other image modalities, all AO images were corrected for magnification error related to axial length variation using the modified Littmann's method described by Bennett et al, 18 as per the equation: q = 0.013063 × (axial length in mm − 1.82), where q is the magnification factor for that eye. Refer to Chew et al 19 for more details. Retinal regions of interest (ROI) were chosen to coincide with microperimetry test loci from the three testing grids.…”
Section: Adaptive Optics Flood Illumination Ophthalmoscopymentioning
confidence: 99%
“…The advantages of AO-FIO include its incorporation of a spinning diffuser to eliminate speckle from its light source. Conversely, it is limited by a poor axial resolution (~300 μm), which reduces cone photoreceptor contrast and decreases repeatability of longitudinal cone density measurements [42,43]. The efficiency of AO-FIO was previously restricted by its long imaging time per frame due to light source and detector technologies.…”
Section: Retinal Imaging Modalities Using Adaptive Opticsmentioning
confidence: 99%